Understanding Inflammatory Responses in the Manifestation of Prothrombotic Phenotypes - Chanchal, Shankar; Mishra, Aastha; Singh, Manvendra Kumar; Ashraf, Mohammad Zahid (Frontiers in Cell and Developmental Biology, 2020)
Inflammasome complex is a multimeric protein comprising of upstream sensor protein of nucleotide-binding oligomerization domain-like receptor family, an adaptor protein apoptosis-associated speck-like protein and downstream effector cysteine protease procaspase-1. Its normal activation is responsible in pathogen defense but abnormal activation of inflammasomes results in many inflammatory and cardiovascular disorders including thrombosis. It has displayed a prominent role in the clot formation advocating an interplay between inflammation and coagulation cascades. Therefore, the elucidation of inflammasome and its molecular mechanisms in the manifestation of prothrombotic phenotypes becomes pertinent. Thrombosis is the formation and propagation of blood clot in the arterial or venous system due to several interactions of vascular and immune factors. It is considered as the third most common disease after coronary artery disease and stroke, which are responsible for mortality worldwide. Recently several studies have established a strong connection of inflammatory processes with this blood coagulation disorder. The hemostatic balance in thrombosis gets altered by the inflammatory mechanisms resulting in endothelial and platelet activation and increased secretion of von Willebrand factor, tissue factor (TF), P-selectin and many more. The upregulation of these factors is the critical event in the pathogenesis of thrombosis. Among various inflammasome, nucleotide-binding domain, leucine-rich-containing family, pyrin domain containing 3 (NLRP3) is one of the best-studied sterile inflammasomes that has documented a link between inflammation and coagulation in thrombosis. NLRP3 activation results in the catalytic conversion of procaspase-1 to active caspase-1, which facilitate the maturation of interleukin-1β and interleukin-18. These cytokines are responsible for platelet activation and aggregation and increases the susceptibility to thrombosis. However, its molecular mechanism related to the pathogenesis of these disorders is still elusive. There have been several reports that demonstrate TF mediated signaling in the production of pro-inflammatory cytokines. In addition, TF enhances inflammation by activating protease-activated receptors on various cells, which lead to additional cytokine expression. Therefore, it would be illuminating to interpret the inflammasomes regulation in TF mediated coagulation and inflammation. This review, thus, tries to comprehensively compile emergent regulatory roles of the inflammasomes in thrombosis and discusses their molecular pathways in the manifestation of thrombotic phenotypes.